2014
DOI: 10.4315/0362-028x.jfp-14-220
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Of Shiga Toxigenic Escherichia coli Relevant to Lettuce Washing Processes and Consideration Of Factors for Evaluating Washing Process Surrogates

Abstract: Postharvest processes for fresh produce commonly include washing in water containing antimicrobial chemicals, such as chlorine; however, if the antimicrobials are not present in sufficient levels, washing can promote the spread of contamination that might be present. To understand cross-contamination risk during washing, we tested a collection of Shiga toxigenic Escherichia coli (STEC), including O157:H7 and other non-O157 strains, for certain traits during washing of fresh-cut lettuce, i.e., sensitivity to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In our study, we also identified variability in chlorine tolerance among strains of EHEC. Differences in sanitizer tolerance among serotypes and/or genetic subtypes of foodborne pathogens have been reported for EHEC [38,39]. Shen et al examined variation in chlorine tolerance in produce wash water among multiple serotypes of Salmonella and Shiga toxin-producing E. coli (STEC), and found, consistent with our day 0 findings, that among STEC, O157:H7 strains were more tolerant than the non-O157 STEC tested [39].…”
Section: Discussionsupporting
confidence: 77%
“…In our study, we also identified variability in chlorine tolerance among strains of EHEC. Differences in sanitizer tolerance among serotypes and/or genetic subtypes of foodborne pathogens have been reported for EHEC [38,39]. Shen et al examined variation in chlorine tolerance in produce wash water among multiple serotypes of Salmonella and Shiga toxin-producing E. coli (STEC), and found, consistent with our day 0 findings, that among STEC, O157:H7 strains were more tolerant than the non-O157 STEC tested [39].…”
Section: Discussionsupporting
confidence: 77%
“…Transfer from contaminated leaves to wash water (58) and attachment to cleaned leaves (24) have been studied as relevant behaviors in the survival of E. coli O157:H7 in fresh produce processes. Characteristics for surrogate behavior that might be relevant in a cross-contamination event include inactivation by the antimicrobial agent, as well as ability to detach from and attach to leaves in a washing process (14). When such a surrogate has been identified, an option 1 validation could be performed by product inoculation, representing the worst-case pathogen contamination load reasonably likely to be introduced to the process.…”
Section: Process Validation For Preventive Controlsmentioning
confidence: 99%
“…However, suitable/qualified surrogates for validating the performance of ffFVHs handing and processing operations are presently lacking (Gombas et al., 2017). Therefore, specific studies will be needed to qualify a potential surrogate microorganism showing a similar behaviour as compared to the target pathogen (Deng et al., 2014). Moreover, challenge testing is costly, especially as all deviations of the process must be considered to cover the variability range of relevant operating conditions (as defined in step [2]) within and between production batches/runs.…”
Section: Assessmentmentioning
confidence: 99%